Emerging from the rubble of postcolonial studies: Book history and Australian literary studies - Henningsgaard, Per (2016)
Scholars of Australian literature have engaged more frequently and enthusiastically with book history approaches than nearly any other postcolonial nations literary scholars. Several Australian scholars have suggested that book history has taken over where postcolonial studies left off. In their choice of subject matter, however, Australian book historians reinforce the very constructions of literary value they purport to dismantle, similar to how scholars of postcolonial studies have been critiqued for reinforcing the construction of colonial identities. Thus, this article looks to the intellectual history of postcolonial studies for examples of how it has responded to similar critiques. What is revealed is a surprising, and heretofore untold, relationship between book history and postcolonial studies, which focuses on their transnational potential versus their ability to remain firmly grounded in the national.